The potential of the BBNJ clearing house mechanism to enhance knowledge pluralism in marine carbon dioxide removal assessment - Boettcher, Miranda; Brent, Kerryn (Frontiers in Climate, 2024)
As the global community intensifies efforts to achieve net-zero greenhouse gas emissions, active carbon dioxide removal (CDR) is being planned alongside emission reductions. The open ocean, which already absorbs a substantial portion of anthropogenic carbon dioxide, is increasingly seen as a promising site for various types of marine CDR (mCDR). All of these approaches are in the preliminary stages of development, and many questions remain with regard to their assessment and governance. This paper discusses the potential role of the newly established Agreement on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction (BBNJ Agreement) in assessing and governing mCDR. A step-by-step mapping of the various stages of the BBNJ environmental impact assessment process shows that the new Clearing House Mechanism (CHM) could facilitate knowledge pluralism and contribute to the holistic assessment of mCDR proposals. The paper concludes by identifying challenges in operationalizing the CHM and putting forward recommendations to strengthen its capacity for fostering knowledge pluralism in decision-making on mCDR research and implementation.